BETWEEN MEMORY, ALTERITY, AND FORM: REFLECTIONS ON THE TRANSLATION PROCESS OF SOLO QUEDA SALTAR (2018), BY MARÍA ROSA LOJO, INTO BRAZILIAN PORTUGUESE - Mangueira, Maria Josele Coelho; Mello, Kátia Rodrigues (Seven Editora, 2026)
This article analyzes the process of translating into Portuguese the novel Solo queda saltar (2018), by María Rosa Lojo, which has not yet been published in Portuguese within the Brazilian literary system, from a perspective that articulates ethics, form, and cultural mediation. Grounded in the contributions of Antoine Berman (2007), Lawrence Venuti (2008), Gideon Toury (1995), and Eugene Nida (1964), the study discusses the construction of a translation project oriented toward preserving alterity, the plurality of narrative voices, and the formal density of the source text. The adopted methodology integrates hermeneutic reading, stylistic analysis, and systematic recording of translation decisions throughout the process, configuring a practice-based approach. Based on the analysis of concrete choices—such as the translation of the title, the treatment of temporal regimes, and the use of paratextual resources—the study examines dilemmas, losses, and mediation strategies involved in transferring the novel into Portuguese. It argues that literary translation, understood as an interpretative, ethical, and situated practice, also constitutes a form of knowledge production. The study thus contributes to the debate on translational authorship, applied methodology, and translation as rewriting within the Brazilian context.